Ultrasonic Density of Kidneys in Healthy Children and Children with Pyelonephritis - L.I. Vakulenko; V.A. Kondratiyev; A.V. Vakulenko; I.I. Andreychenko (Zaslavsky O.Yu., 2014)
The aim of the research - development of quantitative standard indices of ultrasonic density of a kidney in healthy children and definition of its changes at pyelonephritis. Ultrasonic research of kidneys with the subsequent computer processing of ultrasonic scans and determination of coefficients of ultrasonic density of kidneys of 90 healthy children from 1 to 16 years is conducted. Age ranges of ultrasonic density of a kidney and its structures in healthy children are determined, these age ranges were used further as standards. It is revealed that the tendency to decrease in ultrasonic density of renal capsule and pelvis is observed with age from the parenchyma at children from 6 to 12 years. The assessment of indicators of ultrasonic density of a kidney at 40 children with pyelonephritis is carried out. At children with acute pyelonephritis moderate increase of ultrasonic density of a capsule and sharp increase of coefficient of ultrasonic density of the renal pelvis was registered. The ultrasonic density of cortical substance at acute pyelonephritis decreased in 86.4 % of cases, and medullary substance - in 61.1 % of cases. The ultrasonic density of tubules decreased slightly, but in 72 % of cases. At chronic pyelonephritis in the period of the exacerbation the changes of ultrasonic density were similar: moderate increase of ultrasonic density of renal capsule and pelvis that was accompanied by moderate decrease in ultrasonic density of cortical and medullar substance.